Danish Greylag Goose Anser anser use of the Coto Doñana sand dunes for gritting - Fox, Anthony D.; Heldbjerg, Henning; Clausen, Kevin K.; Therkildsen, Ole R.; Zhao, Qingshan; Negro, Juan J.; Green, Andy J. (Wildfowl, 2023)
Four adult female Greylag Geese Anser anser tagged with GPS/GSM tracking devices in East Jutland, Denmark migrated to spend the winter of 2021/22 in Coto Doñana, southern Spain. Regular 10-min GPS positions confirmed that three out of the four birds visited the famous Cerro de los Ánsares (“Hill of the Geese”) on 1–4 different dates during their time in the study area (total duration = 12–95 days). They almost certainly did so to gather grit to aid digestion (as observed and described in the literature), confirming the persistence of this behaviour reported anecdotally over at least two centuries. The visits of 10–50 min duration were most often immediately after sunrise (although one short visit out of nine total visits occurred in the afternoon) and usually occurred from and to adjacent pools north of the dune system, where the geese feed traditionally on Alkali Bulrush Bolboschoenus maritimus. The relatively infrequent visits to the dunes, together with the lack of visits by the fourth bird and also by a Swedish-tagged bird from another study, imply that the geese can obtain grit from other sources within their feeding areas in the marshes and on rice Oryza sp. fields in the vicinity. The observations, however, also confirm that this part of the dune system remains an important source of grit for birds feeding nearby, although why they do so here and not elsewhere in the 30 km long and 2–4 km wide dunes remains unclear.